Morphological evidence for the presence of the Danube Crested Newt, Triturus dobrogicus (Kiritzescu, 1903), in Slovenia - David Stanković; Teo Delić (Natura Sloveniae)
We offer preliminary reports on the presence of the Danube Crested Newt, Triturus dobrogicus, in Slovenia. This species reaches its western border of distribution in Hungary, Austria and Croatia, but untill recently it was not known from Slovenia. Here we report on the first record of this species in Slovenia, found in Dolinsko polje of the Prekmurje region during the herpetological surveys carried out in the spring of 2009 and 2010. The species identity was determined by coloration, body shape and the Wolterstorff Index values. Only with additional genetic analysis could we answer if this is a pure population or whether hybridisation with T. carnifex is present.